Towards best practice during COVID-19: A responsive and relational program with remote schools to enhance the wellbeing of Aboriginal and Torres Strait Islander students. (April 2023) - McCalman, Janya; Caelli, Nicole; Travers, Helen; Graham, Veronica; Hunter, Ernest
Purpose: From 2018, the Schools Up North (SUN) programme worked with three remote Australian schools to enhance their capability and resilience to support the wellbeing and mental health of Aboriginal and Torres Strait Islander students and staff. This paper explores the implementation of SUN during the first two years of COVID-19 (2020–2021). Method: Using grounded theory methods, school staff, other service providers and SUN facilitators were interviewed, with transcripts and programme documents coded and interrelationships between codes identified. An implementation model was developed. Results: The SUN approach was place-based, locally informed and relational, fostering school resilience through staff reflection on and response to emerging contextual challenges. Challenges were the: community lockdowns and school closures; (un)availability of other services; community uncertainty and anxiety; school staff capability and wellbeing; and risk of educational slippage. SUN strategies were: enhancing teachers' capabilities and resources, facilitating public health discussions, and advocating at regional level. Outcomes were: enhanced capability of school staff; greater school-community engagement; student belonging and engagement; a voice for advocacy; and continuity of SUN's momentum. Conclusions: The resilience approach (rather than specific strategies) was critical for building schools' capabilities for promoting students and staff wellbeing and provides an exemplar for remote schools globally.